Penegakan Hukum dan Transformasi Agraria Tahun 2024 dalam Upaya Mengatasi Mafia Tanah dan Konflik Pertanahan di Indonesia - Indrawati, Ana (Riwayat: Educational Journal of History and Humanities, 2025)
Law enforcement and agrarian transformation are crucial issues in overcoming land mafia problems and land conflicts in Indonesia. This article discusses agrarian policies implemented in 2024, the effectiveness of law enforcement, as well as strategies for dealing with land mafias and land conflicts. The research method used is a qualitative approach with literature study and policy analysis. The research results show that even though there are stricter agrarian reform policies, implementation in the field still faces challenges, especially in terms of coordination between institutions and law enforcement which is not yet optimal. Therefore, synergy is needed between the government, law enforcement officials and the community to ensure the sustainability of agrarian transformation in Indonesia.